Experimental and computational analysis of stall cells on rectangular wings - Marinos Manolesos (Wind Energy, 2014)
The present paper is the second part of a combined (experimental and computational) study on stall cells (SCs) on a rectangular wing. In the first part, tuft data were used in order to geometrically characterize a stabilized SC resulting from a localized spanwise disturbance introduced by a zigzag tape. Here, pressure measurements on the model and in the wake and aerodynamic polars at midspan are reported. The wing model had an aspect ratio value of 2, the Reynolds number was 106 and the range of angles of attack (α) was from −6° to 16°. Experimental results confirm previous findings. Furthermore, two‐dimensional and three‐dimensional Reynolds Averaged Navier‐Stokes RANS simulations are used in order to better understand the structure of SCs. 3D simulations reproduce the experimental data with a 3° delay in α and permit a qualitative analysis. It is found that the SC vortices start normal to the wing surface and extend downstream in the wake; the evolution of the SC vortices in the wake is in strong interaction with the separation line vortex and the trailing edge line vortex; as the SC vortex develops downstream in the wake, its centreline is contracted towards the SC centre; the wing wake is pushed upstream at the centre of the SC and downstream at the sides by the SC vortices; spanwise lift and drag distributions always attain their minimum at the SC centre.